COMPLEMENTARY THERAPY FOR POST PARTUM PATIENTS WITH HISTORY OF SAVERE PREECLAMSIA A RAPID REVIEW - Lilis Mamuroh; Gina Utami; M. Azka Fahrez; Mustatiah Nurul M; Sani Ailla Azura; Utami Husni; Sukmawati Sukmawati (Journal of Maternity Care and Reproductive Health, 2026)
Preeclampsia is one of the leading causes of maternal mortality in Indonesia. If left untreated, it can lead to complications that may result in the death of both the mother and the fetus. Complementary therapies have emerged as a non-pharmacological alternative to support the mother’s physiological and psychological well-being. This literature review aims to identify complementary therapies for post partumwomen with a history of savere preeclampsia. interventions as non-pharmacological nursing care to support ph.This study employed a rapid literature review design with a systematic search of five databases (PubMed, Scopus, EBSCO, CINAHL, and Emerald Insight) using the PICO framework. Inclusion criteria included full-text articles in English published in the last 5 years. Six key articles were selected for critical analysis The findings indicate that various complementary therapies have significant positive effects. Relaxation interventions (Guided Imagery, PMR, Yoga) have been shown to improve coping mechanisms and lower blood pressure. Aromatherapy and massage therapy is effective in reducing post-cesarean pain and anxiety. In addition, structured nutritional interventions and a combination of traditional and modern treatments have been shown to improve kidney function and reduce inflammatory markers and oxidative stress.: Holistic complementary therapies hold great potential in maternal nursing care to improve clinical outcomes and quality of life for postpartum mothers with a history of severe preeclampsia. Keywords: Complementary therapy, postpartum, severe preeclampsia.